On the derivation of a general thermodynamic expression for the reaction rate constant for cosolvent reaction systems. Issue 12 (1st October 2018) - Wiseman, F. L.; Scott, D. W.; Tamine, J.; O'Connell, R.; Smarra, A.; Mitchell, N.
Abstract: This article presents the derivation of the thermodynamic expressions for the activation free energy and reaction rate constant for cosolvent reaction systems. These expressions account for the factors that are specific to solution‐phase reactions, which include isotropic electrostatic effects and close‐range solvent−solute interactions. This article discusses the idea that electrostatic effects can be correlated with the isotropic relative permittivity, and solvent−solute interactions can be correlated with the cosolvent mole fraction. This article also shows that this type of thermodynamic analysis is necessary for understanding certain nuances of solution‐phase reaction processes not tractable by other types of analyses.